Break monopoly of polarization: CD301b+ macrophages play positive roles in osteoinduction of calcium phosphate ceramics. (September 2021) - Wang, Jiaolong; Zhao, Qin; Zheng, Shihang; Wang, Jinyang; Fu, Liangliang; Wang, Can; Zhao, Zifan; Zhang, Yufeng
Highlights: CD301b+ macrophages are independent of M1/M2 polarization for osteoinduction. Osteoinduction induced by CaP ceramics highly correlated with CD301b+ macrophages. CD301b+ macrophages were beneficial to osteogenic differentiation. CD301b was tailored to reveal effect of regenerative macrophage on osteoinduction. Abstract: The pro-inflammatory M1 and anti-inflammatory M2 polarization macrophages were considered crucial during the immune regulation of bone regeneration. However, M2 polarization macrophages cannot strictly represent regenerative macrophage phenotypes. There is an urgent need to classify a reliable regenerative macrophage to guide the development of osteoimmune modulation and bone regeneration biomaterials. Herein, we report a new CD301b+ macrophage phenotype in the osteoinduction process of calcium phosphate ceramics. There were far more CD301b+ macrophages around biphasic calcium phosphate ceramics than those around β-tricalcium phosphate ceramics. Additionally, CD301b-deficient mice failed to form new bone around biphasic calcium phosphate ceramics. Moreover, macrophages stimulated by biphasic calcium phosphate ceramics were beneficial to osteogenic differentiation of mesenchymal stem cells. CD301b+ macrophages can activate the IGF1R/Akt/mTOR pathway of mesenchymal stem cells by IGF1 expression, thereby promoting osteogenic differentiation. Furthermore, transplanting the sorted CD301b+ macrophages could further facilitate the osteoinduction of biphasic calcium phosphate ceramics. These data highlighted the critical role of CD301b+ macrophages in the osteoinduction of calcium phosphate ceramics. It may provide a novel target for potential osteoimmune modulation in bone regeneration. Graphical abstract: Image, graphical abstract